Project Based Learning Model on Critical Thinking Skills in Elementary School: Model Pembelajaran Berbasis Proyek untuk Mengembangkan Keterampilan Berpikir Kritis di Sekolah Dasar - Rizmayannudin, Faradya; ZULIKHATIN NUROH, ERMAWATI (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Critical thinking is an essential skill that enables learners to analyze information and solve problems effectively, and it is a crucial competence emphasized in the current educational paradigm. Specific Background: However, elementary school learners often demonstrate limited critical thinking ability due to conventional learning approaches that provide fewer opportunities for inquiry and problem solving. Knowledge Gap: Previous studies have examined Project Based Learning (PJBL) in various contexts, yet limited evidence explores its practical implementation in elementary schools within the framework of religious-based institutions. Aims: This study aims to describe the implementation of PJBL in fostering critical thinking skills among fourth-grade learners at SD Muhammadiyah 1 Taman, Sidoarjo, Indonesia. Results: Using a qualitative case study involving two teachers and five students, data were collected through observation, interviews, and documentation. Findings reveal that learners actively engaged in asking critical questions, demonstrating improved logical reasoning, and presenting project outcomes effectively. Novelty: This study highlights the integration of PJBL across both general and religious subjects, which has been scarcely reported in prior literature. Implications: The results provide insights for educators and policymakers to adopt PJBL as a sustainable approach for strengthening higher-order thinking skills in elementary education. Highlights: PJBL encourages active questioning and reasoning in elementary learners. Integration of PJBL applied in both general and religious subjects. Provides practical insights for fostering critical thinking in primary education. Keywords: Critical Thinking; Project Based Learning; Elementary Education; Qualitative Case Study; Islamic School